1992
DOI: 10.1007/bf01973632
|View full text |Cite
|
Sign up to set email alerts
|

Receptor alterations in manganese intoxicated monkeys

Abstract: The density of four different receptors and one marker of dopamine uptake sites were analyzed in monkey brains after manganese exposure (0.1 g manganese per month during 26 months, a dose comparable to that workers might inhale in dusty environments) by means of quantitative receptor autoradiography. The binding of 3H-mazindol to the dopamine uptake sites was reduced by 75% in both the head of the caudate nucleus and putamen, while it remained unchanged in the other regions analyzed. The binding of the D1 rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 28 publications
2
39
0
Order By: Relevance
“…Concerning the mechanism of Mn-induced neurotoxicity, the effects of Mn intoxication on the expression of dopamine receptors in the striatum have been examined, but results have been controversial. For example, one study reported that Mn intoxication did not significantly alter DRD2 levels in the striatum of monkeys, 19) while another showed that striatal DRD2 levels markedly decreased in chronic Mn toxicity. 20) We described the behavioral changes and expression of dopamine D2-like receptors induced by acute Mn exposure in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the mechanism of Mn-induced neurotoxicity, the effects of Mn intoxication on the expression of dopamine receptors in the striatum have been examined, but results have been controversial. For example, one study reported that Mn intoxication did not significantly alter DRD2 levels in the striatum of monkeys, 19) while another showed that striatal DRD2 levels markedly decreased in chronic Mn toxicity. 20) We described the behavioral changes and expression of dopamine D2-like receptors induced by acute Mn exposure in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The groups headed by Eriksson in Sweden (1992a) and by Guilarte in the United States (2006aStates ( , 2008, have used this approach extensively because not only is it quantitative, it also offers exquisite anatomical information with high resolution. Eriksson et al (1992a) performed receptor autoradiography studies in the basal ganglia of monkeys exposed to 0.1 g Mn/month for 26 months. They indicated that this dosing regimen was comparable with what workers might inhale in dusty environments.…”
Section: Behavioral Neuroimaging Neurochemical and Neuropathologicmentioning
confidence: 99%
“…Only 6 papers reported group-average neurochemical endpoints of manganese treatment (Ulrich et al 1979a(Ulrich et al , 1979b(Ulrich et al , 1979cBird et al 1984;Eriksson et al 1992a;Neff et al 1969). Evaluation of motor effects was mostly qualitative with only two studies reporting quantitative tests to evaluate motor response (Eriksson et al 1992a;Newland and Weiss 1992).…”
Section: Parameter Values: Non-human Primate Studiesmentioning
confidence: 99%
“…Outcomes to the right of the vertical line were produced by MnO 2 exposure and almost all outcomes to the left by MnCl 2 exposure. Only Bird et al (1984), Eriksson et al 1992a, Neff et al (1969, Ulrich et al (1979aUlrich et al ( , 1979Ulrich et al ( b, 1979c) report average outcomes for more than one animal. Reported outcomes from other studies are from single animals.…”
Section: Figure Captionsmentioning
confidence: 99%